Impact of Digital Accounting Tools on Financial Decisions in Small and Medium Businesses - Mohammad Emran Abu Afifeh; Ayşem İyikal Çelebi (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
Digital accounting tools play important roles for small business owner’s financial decision. The benefit of these tools ranges from ease of financial reporting, better record keeping, time efficiency, budgeting, expense control, profitability analysis and business growth planning. Small businesses in Northern Cyprus are faced with challenges such as time inefficiency, low level of organization, poor record keeping, inadequate budgeting planning, expense control, limited resource, and tax compliance. These challenges stem from inadequate tools for keeping accurate data of small businesses. The study was intent on investigating how the use of digital accounting tools has affected various facets of accounting in small businesses with the use of extended TAM. The focus was to pinpoint the gains and setbacks associated with implementing them. The research examined the impact and ease digitalization seen in the area of better record keeping, time efficiency, budgeting, expense control, profitability analysis and business growth planning. Qualitative study was undertaken employing a thematic analysis approach, utilizing semi-structured interviews to obtain comprehensive and in-depth insights from professionals and entrepreneurs in different industries and locations. The study revealed that SMEs benefited immensely by using digital accounting tools. Small business owners in Northern Cyprus reported that it improved their ease of doing business (PEU) and overall business organization (PU). Younger business owners in Northern Cyprus below 45 years were observed to participate more in the use of digital accounting compared to older business owners. There is need to sensitize the public about these benefits ranging from budget planning, expense control, cash flow forecasting, profitability analyzing, and business growth analyzing.